Coronary Flow Variations Following Percutaneous Coronary Intervention Affect Diastolic Nonhyperemic Pressure Ratios More Than the Whole Cycle Ratios - Muhammad Aetesam‐ur‐Rahman; Tian X. Zhao; Kitty Paques; Joana Oliveira; Bharat Khialani; Stephen Kyranis; Denise M. Braganza; Sarah C. Clarke; Martin R. Bennett; Nick E. J. West; Stephen P. Hoole (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2022)
Background Post–percutaneous coronary intervention (PCI) fractional flow reserve ≥0.90 is an accepted marker of procedural success, and a cutoff of ≥0.95 has recently been proposed for post‐PCI instantaneous wave‐free ratio. However, stability of nonhyperemic pressure ratios (NHPRs) post‐PCI is not well characterized, and transient reactive submaximal hyperemia post‐PCI may affect their precision. We performed this study to assess stability and reproducibility of NHPRs post‐PCI. Methods and Results Fifty‐seven patients (age, 63.77±10.67 years; men, 71%) underwent hemodynamic assessment immediately post‐PCI and then after a recovery period of 10, 20, and 30 minutes and repeated at 3 months. Manual offline analysis was performed to derive resting and hyperemic pressure indexes (Pd/Pa resting pressure gradient, mathematically derived instantaneous wave‐free ratio, resting full cycle ratio, and fractional flow reserve) and microcirculatory resistances (basal microvascular resistance and index of microvascular resistance). Transient submaximal hyperemia occurring post‐PCI was demonstrated by longer thermodilution time at 30 minutes compared with immediately post‐PCI; mean difference of thermodilution time was 0.17 seconds (95% CI, 0.07–0.26 seconds; P=0.04). Basal microcirculatory resistance was also higher at 30 minutes than immediately post‐PCI; mean difference of basal microvascular resistance was 10.89 mm Hg.s (95% CI, 2.25–19.52 mm Hg.s; P=0.04). Despite this, group analysis confirmed no significant differences in the values of resting whole cycle pressure ratios (Pd/Pa and resting full cycle ratio) as well as diastolic pressure ratios (diastolic pressure ratio and mathematically derived instantaneous wave‐free ratio). Whole cardiac cycle NHPRs demonstrated the best overall stability post‐PCI, and 1 in 5 repeated diastolic NHPRs crossed the clinical decision threshold. Conclusions Whole cycle NHPRs demonstrate better reproducibility and clinical precision post‐PCI than diastolic NHPRs, possibly because of less perturbation from predominantly diastolic reactive hyperemia and left ventricular stunning. Registration URL: https://clinicaltrials.gov/ct2/show/NCT03502083; Unique identifier: NCT03502083 and URL: https://clinicaltrials.gov/ct2/show/NCT03076476; Unique identifier: NCT03076476.